Reprodutibilidade de questionários de qualidade de vida relacionada à saúde bucal (SOHO-5 e OHIP-14) - Oliveira, Marcos Alexandre Casimiro de. (2015)
The use of questionnaires in epidemiological studies has allowed a broader knowledge of the adverse oral conditions that affect the quality of life. This way, may be important ally to development of public health politics and strategies of prevention and treatment. Thus, the objective of this paper was to evaluate the reproducibility of oral health-related quality of life, SOHO-5 (Scale Oral Health Outcomes for Five-Year-Old Children – children version) for 5-years-old children and OHIP- 14 (Oral Health Impact Profile) for 12 years school applied to public school students of a small city of Paraiba outback. To this end, an only examiner (intra-examiner kappa = 0.82) had a census of all children available, totaling 59 students with 05 years and 39 to 12 years who underwent a clinical examination based on World Health Organization criteria to dental cavity (DMFT) and application of a quality of life questionnaire related to oral health. After the thirty-day period, this process was repeated reproduction of the same application conditions. As the results, it was found that the variables of the SOHO-5: “difficulty playing” (kappa=-0,042); “difficulty eating” (kappa=0,112); “difficulty drinking” (kappa=0,028) and “difficulty sleeping” (kappa=0,184) showed more vulnerable in the two moments assessment questionnaire. The OHIP-14 showed regular agreement for the item: "he was worried because of problems with their teeth/her mouth" (kappa=0,256), and moderate agreement for "problem to speak a word" (kappa = 0.505), "pain in your mouth and teeth" (kappa = 0.408), "for your meals" (kappa = 0.437) and "felt ashamed" (kappa = 0.402). There was no correlation between the response pattern of children under 5 years in both the questionnaire application moments for all items and agreement to regulate moderate between the responses of children under 12. However, although of changing the standard of responses, the OHIP-14 showed better reproducibility than the SOHO-5.